A piezoelectric-based energy harvester for video game system controller - Teo, Andrew Chen Siong. (2012)
The issues on the imminent crisis of fast depleting non-renewable energy and the raging concerns on environmental climate change associated with global warming due to the excessive greenhouse gas emission (CO2 and others) from the way energy are generated today are the motivation and driving force behind clean energy generation.